Antimicrobial and enhancement of the antibiotic activity by phenolic compounds: Gallic acid, caffeic acid and pyrogallol. (October 2016) - Lima, Valéria N.; Oliveira-Tintino, Cícera D.M.; Santos, Enaide S.; Morais, Luís P.; Tintino, Saulo R.; Freitas, Thiago S.; Geraldo, Yuri S.; Pereira, Raimundo L.S.; Cruz, Rafael P.; Menezes, Irwin R.A.; Coutinho, Henrique D.M.
Abstract: The indiscriminate use of antimicrobial drugs has increased the spectrum of exposure of these organisms. In our studies, these phenolic compounds were evaluated: gallic acid, caffeic acid and pyrogallol. The antibacterial, antifungal and modulatory of antibiotic activities of these compounds were assayed using microdilution method of Minimum Inhibitory Concentration (MIC) to bacteria and Minimum Fungicide Concentration (MFC) to fungi. The modulation was made by comparisons of the MIC and MFC of the compounds alone and combined with drugs against bacteria and fungi respectively, using a sub-inhibitory concentration of 128 μg/mL of substances (MIC/8). All substances not demonstrated clinically relevant antibacterial activity with a MIC above ≥1024 μg/mL. As a result, we observed that the caffeic acid presented a potentiating antibacterial effect over the 3 groups of bacteria studied. Pyrogallol showed a synergistic effect with two of the antibiotics tested, but only against Staphylococcus aureus . In general, caffeic acid was the substance that presented with the greatest number of antibiotics and with the greatest number of bacteria. In relation to the antifungal activity of all the compounds, the verified results were ≥1024 μg/mL, not demonstrating significant activity. Regarding potentiation of the effect of fluconazole, was observed synergistic effect only when assayed against Candida tropicalis, with all substances. Therefore, as can be seen, the compounds presented as substances that can be promising potentiating agents of antimicrobial drugs, even though they do not have direct antibacterial and antifungal action. Highlights: The pyrogallol reduces the concentration necessary to kill all population of Candida albicans . All substances reduced the concentration necessary to kill all population of Candida tropicalis . The caffeic acid potentiated the antibiotic activity against all bacterial strains. The pyrogallol and gallic acid potentiated the antibiotic activity only against Staphylococcus aureus .